Illicit use of methadone and buprenorphine among adolescents and young adults in Sweden - Richert, Torkel; Johnson, Björn ; 0000-0002-1601-2706 (Harm Reduction Journal, 2013)
Background Illicit use of methadone and buprenorphine has been described as a growing problem in Sweden in recent years, and has been associated with an increased drug-related mortality. Critics claim that the substances have become popular among adolescents and that they function as a gateway to heroin use. The aim of this study is to investigate, firstly, the extent to which illicit use of methadone and buprenorphine occurs among adolescents and young adults in Sweden, and secondly, at what stage in a user's drug career these substances tend to appear. Methods The study is based on surveys and structured interviews on drug use among various populations of young people, in addition to qualitative interviews with 86 informants who, in their professional capacity, encounter adolescents or young adults who are using illicit drugs. Results Illicit use of methadone and buprenorphine is rare among young people in Sweden. According to high school surveys, less than 0.1% have tried these substances. Among young drug users in general, few have tried the substances, and there is nothing to indicate that they act as gateway drugs. Among adolescents and young adults with severe drug problems, however, the illicit use of methadone and buprenorphine is more common (54% in a compulsory care sample). These substances normally enter the drug career late, and few use them as their main drug of choice. Other prescription drugs, like benzodiazepines and tramadol, are used by adolescents to a far greater extent. Diversion and illicit use of methadone and buprenorphine is not seen as a serious problem by the professionals interviewed. A general view is that the substances are mainly used by people with a heroin or polydrug addiction, often for ""self-medication"" purposes. However, several informants express concern that methadone and buprenorphine may cause fatalities among young drug users without an opioid tolerance. Conclusions Illicit use of methadone and buprenorphine among young drug users is not a widespread problem in Sweden. Harm-reduction measures should target drug users with more severe problems, among whom illicit use of methadone and buprenorphine is more common and pose a medical risk. Illicit use of other prescription drugs, which are less controlled and more widely used by young people, is an important issue for further research.
2024-02-15T13:28:39.251+01:00
Keywords: Methadone; Buprenorphine; Diversion; Illicit use; Adolescents; Young adults; Drug career; Medical and Health Sciences; Medicin och hälsovetenskap